Estimation of inter-fractional variations in interstitial multi-catheter breast brachytherapy using a hybrid treatment delivery system - Kallis, Karoline; Abu-Hossin, Nadin; Kreppner, Stephan; Lotter, Michael; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph (Radiotherapy and Oncology, 2019)
Purpose: Irradiation of the tumor bed using interstitial multi-catheter brachytherapy is one of the treatment options for breast cancer patients. In order to ensure the planned dose delivery an advanced quality intervention method using an electromagnetic tracking (EMT) system is presented. The system is used to assess inter-fractional variations within the framework of a patient study. Methods and materials: Until now 41 patients were included in the study for the evaluation and overall 355 EMT measurements were performed. The catheter traces are measured automatically and sequentially using an afterloader prototype (Flexitron, Elekta, Veenendaal, The Netherlands) equipped with an EMT sensor. The implant geometry is tracked directly after implantation, after CT imaging and after each irradiation fraction. The acquired data is rigidly registered to the catheter traces defined in the treatment plan and the dwell positions (DP) are reconstructed. DPs defined in treatment planning serve as reference. Breathing motion was corrected and recorded using three reference 6DoF sensors placed on the patients’ skin. The Euclidean distance between the planned and reconstructed DPs provides information about possible inter-fractional deviations. Further, the influence of various factors on the occurrence of large deviations was investigated, like the patients’ age, the length of the catheter, the breast volume, etc. Results: Over all patient measurements a median Euclidean distance of 2.19 mm was determined between the reconstructed DPs and the reference DPs. The median deviation combining all datasets was minimal (1.67 mm) at the measurement directly after CT imaging. The deviations between the different fractions have a median distance of 2.31 mm which could be improved to 2.05 mm by adapting the treatment plan according to the follow-up CT. No correlation between the distance to the skin, ribs, mammilla or the breast volume and the occurrences of large deviations was found. The largest deviations were determined in the upper inner quadrant of the breast. Conclusion: The afterloader prototype could be well integrated into the clinical routine and is beneficial for ensuring the quality of the brachytherapy. Overall, a small median DP deviation, lower than the used step size of 2.5 mm, was detected.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Breast cancer; Electromagnetic tracking; Inter-fractional variations; Interstitial multi-catheter brachytherapy